Anti-aging insulated power cable
By coating nano-silica onto the surface of kaolin and grafting ultraviolet absorbers, a composite filler was constructed, which solved the problem of aging of insulating materials due to ultraviolet radiation and thermo-oxidative stress, and achieved long-term stability and improved mechanical properties of the insulating materials.
Patent Information
- Application Number
- CN202511201157.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-26
- Publication Date
- 2025-10-28
AI Technical Summary
Existing insulation materials age due to factors such as ultraviolet radiation, heat, and oxygen during long-term use, resulting in performance degradation. Traditional additives are prone to decomposition, volatilization, or migration, thus losing their effectiveness.
Modified kaolin was used as a composite filler. By coating the surface of kaolin with nano-silica and grafting ultraviolet absorbers, an ultraviolet shielding and thermally stable interface was constructed. The multi-scale interfacial interaction between SiO2@kaolin and polymer was utilized to enhance mechanical properties and resistance to environmental stress cracking.
It significantly improves the UV aging stability and thermal stability of insulating materials, maintains the dimensional stability and mechanical integrity of materials during long-term operation, and reduces failures and accidents caused by aging.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of cable technology, and more specifically, to an aging-resistant insulated power cable. Background Technology
[0002] As a crucial carrier for power transmission and distribution, the performance of power cables directly affects the safe and stable operation of the power system. Among the many performance indicators of power cables, insulation performance and aging resistance are particularly important. Cables with good insulation performance can effectively prevent current leakage and ensure the efficiency of power transmission; while aging resistance determines whether the cable can maintain stable insulation performance during long-term use, reducing faults and accidents caused by aging.
[0003] Although cross-linked polyethylene (XLPE) and ethylene propylene rubber (EPR) have certain aging resistance properties, they are still subject to aging due to factors such as heat, light, and oxygen during long-term operation. For example, XLPE is prone to thermo-oxidative aging at high temperatures, leading to molecular chain breakage and decreased insulation performance; EPR undergoes photo-oxidative aging under ultraviolet radiation, causing the rubber to harden, become brittle, and lose elasticity. To improve the aging resistance of insulation materials, various additives are usually added. However, these additives may decompose, volatilize, or migrate during long-term use, thus losing their intended function. To solve the above technical problems, this invention proposes a new aging-resistant insulated power cable. Summary of the Invention
[0004] This invention proposes an aging-resistant insulated power cable, which solves the problem that ultraviolet absorbers may decompose, volatilize, or migrate and fail during long-term use, thereby improving the aging resistance stability of the insulation material during long-term operation.
[0005] The technical solution of the present invention is as follows: In a first aspect, the present invention proposes an aging-resistant insulated power cable, comprising a conductor layer and an aging-resistant outer sheath layer arranged sequentially from the inside out. The aging-resistant outer sheath layer comprises the following raw materials in parts by weight: 55-65 parts of PVC resin, 20-30 parts of EPDM rubber, 10-15 parts of ethylene-vinyl acetate copolymer, 10-12 parts of modified kaolin, 18-20 parts of diisononyl phthalate, 4-5 parts of calcium-zinc composite stabilizer, 1.5-2 parts of antioxidant, 0.5-1 part of polyethylene wax, and 0.5-0.7 parts of calcium stearate. The modified kaolin is obtained by coating the surface of kaolin with nano-silica to obtain SiO2@kaolin and grafting an ultraviolet absorber.
[0006] In the formulation of the aging-resistant outer sheath, PVC resin, ethylene propylene diene monomer (EPDM) rubber, and ethylene-vinyl acetate copolymer (EVA) constitute a ternary matrix system. PVC provides a rigid framework and chemical resistance, EPDM imparts flexibility and ozone resistance, and EVA improves processing flowability and low-temperature performance through vinyl acetate segments. The three components complement each other through their polarity differences: the polar chlorine atoms of PVC interact with the ester groups of EVA via dipole-dipole interactions, while the non-polar segments of EPDM bond with the hydrophobic surface of modified kaolin using van der Waals forces. Modified kaolin acts as a multifunctional additive in this system: its surface-coated SiO2 nanolayer enhances compatibility with the chlorine atoms of PVC through hydrogen bonding, while the grafted UV absorber molecular chains penetrate into the non-polar regions of EPDM / EVA, forming physical entanglements. This multi-scale interfacial interaction significantly improves filler dispersibility and reduces stress concentration points, thereby synergistically enhancing mechanical properties and resistance to environmental stress cracking.
[0007] As a further technical solution, the preparation steps of SiO2@kaolin include: mixing KH550 with 1 / 10 parts by weight of ethanol, stirring at 400-500 rpm for 10-15 min to form a silane pre-hydrolyzed solution for later use; mixing tetraethyl orthosilicate with the remaining ethanol, adding the silane pre-hydrolyzed solution, and adding ammonia water, stirring at 250-300 rpm for 25-30 min to obtain a reaction solution; adding kaolin to the aforementioned reaction solution and ultrasonically dispersing it, stirring in a constant temperature water bath at 40±2℃ at 250-300 rpm for 3.5-4.5 h, centrifuging, and vacuum drying to obtain the final product.
[0008] As a further technical solution, the mass concentration of the ammonia water is 25-30%.
[0009] As a further technical solution, the weight ratio of KH550, tetraethyl orthosilicate, ethanol, ammonia and kaolin is 0.5-0.7:10-14:80-90:4-5:5-6.
[0010] As a further technical solution, the preparation steps of the modified kaolin include: adding SiO2@kaolin to a toluene solution containing an ultraviolet absorber and a titanate coupling agent, sonicating at 100-150W for 30-40 minutes, stirring at 180-200 rpm under a nitrogen atmosphere, refluxing in an oil bath at 100-110℃ for 5-6 hours, and then filtering, washing, and drying to obtain the modified kaolin.
[0011] As a further technical solution, the ultraviolet absorber is ultraviolet absorber UV326; the titanate coupling agent is NDZ-201.
[0012] As a further technical solution, the weight ratio of SiO2@kaolin, ultraviolet absorber, toluene and titanate coupling agent is 1-1.5:3.5-4.5:100-110:1-1.5.
[0013] As a further technical solution, the antioxidant includes antioxidant 1010 and antioxidant 168 with a weight ratio of 2-3:1.
[0014] The antioxidant system employs a combination of hindered phenols (antioxidant 1010) and phosphites (antioxidant 168). Hindered phenols inhibit thermo-oxidative degradation by providing hydrogen atoms to terminate free radical chain reactions; phosphites, on the other hand, block the oxidation cycle by reducing peroxides to generate stable alcohol products. The synergistic effect of these two agents significantly reduces the chain scission rate of the PVC matrix during thermo-oxidative aging. Simultaneously, the UV absorber UV326 in the modified kaolin absorbs ultraviolet light in the 290-400 nm wavelength range through its π-π conjugated structure and converts it into harmless heat energy. Its grafted structure ensures the steric stability of the UV absorber during the material's service life, avoiding the failure problem caused by photodegradation of traditional small-molecule absorbers.
[0015] Secondly, this invention proposes a method for preparing an aging-resistant insulated power cable, comprising the following steps: mixing PVC resin, EPDM rubber, ethylene-vinyl acetate copolymer, and 1 / 3 by weight of diisononyl phthalate at 110-115°C and 200-250 rpm for 5-8 min; adding modified kaolin, the remaining diisononyl phthalate, stabilizers and antioxidants, polyethylene wax, and calcium stearate, and mixing at 70-80°C and 45-55 rpm for 10-12 min; passing the mixture through a two-roll mill at 80-90°C three times; water-cooling to 40°C and pelletizing; and extruding the mixture using a twin-screw extruder to coat the conductor layer to obtain the aging-resistant insulated power cable.
[0016] As a further technical solution, the temperature of the twin-screw extruder is 145-150℃ in zone I, 160-165℃ in zone II, 170-175℃ in zone III, 180-185℃ in zone IV, and 185±2℃ in the die head.
[0017] The working principle and beneficial effects of this invention are as follows: This invention employs a synergistic strategy of surface coating and chemical grafting to dual-modify kaolin, constructing a composite filler with UV shielding, thermal stability, and interface strengthening functions. First, a nano-silica coating layer is generated in situ on the kaolin surface by catalyzing the hydrolysis of tetraethyl orthosilicate using a silane coupling agent (KH550). This process, via a sol-gel method, forms a three-dimensional network structure, increasing the specific surface area of the kaolin and introducing silanol active sites, providing anchoring points for subsequent grafting reactions. Second, a UV absorber (UV326) is chemically grafted onto the SiO2@kaolin surface using a titanate coupling agent (NDZ-201), forming a stable covalent bond. This design achieves spatial immobilization of the UV absorber and the inorganic carrier, avoiding the migration and volatilization problems of UV absorbers in traditional physical blending. Simultaneously, the layered structure of kaolin extends the UV light scattering path, synergistically improving its UV aging resistance.
[0018] This invention constructs a dense interfacial barrier through dual hydrophobic modification of a SiO2 coating layer and a titanate coupling agent. The surface of the SiO2 coating layer is rich in silanol groups, which are converted into hydrophobic siloxane chains after KH550 silanization treatment, effectively reducing the surface energy of kaolin. At the same time, the long alkyl chains of the titanate coupling agent NDZ-201 form a directional hydrophobic layer at the interface between kaolin and polymer, further hindering water penetration. During humid heat aging, the hydrophobic interface inhibits degradation through the following mechanisms: (1) extending the water diffusion path and reducing the hydrolysis reaction rate constant; (2) reducing the contact probability between water molecules and polymer ester bonds and unsaturated bonds, inhibiting hydrolysis chain scission; (3) counteracting the water plasticizing effect through hydrophobic interactions, maintaining the rigidity of the material. In addition, the nanoscale dispersion of modified kaolin can form physical crosslinking points, restricting the movement of polymer molecular chains and avoiding interfacial debonding caused by water absorption and expansion under humid heat conditions. This hydrophobic design, from the molecular scale to the macroscopic structure, enables the material to maintain dimensional stability and mechanical integrity even at 85℃ / 85%RH. Detailed Implementation
[0019] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0020] It should be noted that the PVC resin used in this invention is from Henan Haochuan Chemical Products Co., Ltd., and its grade is SG5; the ethylene propylene diene monomer (EPDM) rubber is from Dow Chemical (China) Co., Ltd., and its grade is EPDM725P; the ethylene-vinyl acetate copolymer is from DuPont, USA, and its model is EVA40W; and the polyethylene wax is from Guangzhou Binlong Chemical Co., Ltd., and its model is D1100.
[0021] Example 1 This embodiment provides an aging-resistant insulated power cable, which consists of a conductor layer and an aging-resistant outer sheath layer arranged sequentially from the inside out. The aging-resistant outer sheath layer comprises the following raw materials in parts by weight: 60 parts PVC resin, 25 parts EPDM rubber, 12 parts ethylene-vinyl acetate copolymer, 11 parts modified kaolin, 19 parts diisononyl phthalate, 4.5 parts calcium-zinc composite stabilizer, 1.8 parts antioxidant, 0.8 parts polyethylene wax, and 0.6 parts calcium stearate. The modified kaolin is obtained by coating the surface of kaolin with nano-silica to obtain SiO2@kaolin and grafting an ultraviolet absorber. The preparation steps of SiO2@kaolin include: KH550 was mixed with 1 / 10 part by weight of ethanol and stirred at 450 rpm for 2 min to form a silane pre-hydrolyzed solution for later use. Tetraethyl orthosilicate was mixed with the remaining ethanol, the silane pre-hydrolyzed solution was added, and 28% ammonia solution was added. The mixture was stirred at 280 rpm for 28 min to obtain a reaction solution. Kaolin was added to the above reaction solution and ultrasonically dispersed. The mixture was then stirred at 280 rpm for 4 h in a constant temperature water bath at 40 °C. After centrifugation, the mixture was vacuum dried at 60 °C for 24 h to obtain SiO2@kaolin. The weight ratio of KH550, tetraethyl orthosilicate, ethanol, ammonia solution and kaolin was 0.6:12:85:4.5:5.5. SiO2@kaolin was added to a toluene solution containing UV absorber UV326 and titanate coupling agent NDZ-201, and sonicated at 120W for 35 min. The mixture was then refluxed in an oil bath at 105℃ for 5.5 h under a nitrogen atmosphere with stirring at 190 rpm. After filtration, washing, and vacuum drying at 60℃ for 24 h, modified kaolin was obtained. The weight ratio of SiO2@kaolin, UV absorber, toluene, and titanate coupling agent was 1.2:4:105:1.2. Among them, antioxidants include antioxidant 1010 and antioxidant 168 with a weight ratio of 2.5:1; The preparation method of aging-resistant insulated power cable includes the following steps: PVC resin, EPDM rubber, ethylene-vinyl acetate copolymer and 1 / 3 part by weight of diisononyl phthalate are mixed at 112°C and 220 rpm for 6 min; modified kaolin, the remaining diisononyl phthalate, stabilizer and antioxidant, polyethylene wax and calcium stearate are added and mixed at 75°C and 50 rpm for 11 min; the mixture is then passed through a two-roll mill at 85°C three times, water-cooled to 40°C and pelletized; the mixture is then extruded using a twin-screw extruder to coat the conductor layer to obtain the aging-resistant insulated power cable. The temperatures of the twin-screw extruder are 148°C in zone I, 162°C in zone II, 172°C in zone III, 182°C in zone IV, and 185°C in the die.
[0022] Example 2 This embodiment provides an aging-resistant insulated power cable, which consists of a conductor layer and an aging-resistant outer sheath layer arranged sequentially from the inside out. The aging-resistant outer sheath layer comprises the following raw materials in parts by weight: 55 parts PVC resin, 20 parts EPDM rubber, 10 parts ethylene-vinyl acetate copolymer, 10 parts modified kaolin, 18 parts diisononyl phthalate, 4 parts calcium-zinc composite stabilizer, 1.5 parts antioxidant, 0.5 parts polyethylene wax, and 0.5 parts calcium stearate. The modified kaolin is obtained by coating the surface of kaolin with nano-silica to obtain SiO2@kaolin and grafting an ultraviolet absorber. The preparation steps of SiO2@kaolin include: KH550 was mixed with 1 / 10 part by weight of ethanol and stirred at 400 rpm for 10 min to form a silane pre-hydrolyzed solution for later use. Tetraethyl orthosilicate was mixed with the remaining ethanol, the silane pre-hydrolyzed solution was added, and 25% ammonia solution was added. The mixture was stirred at 250 rpm for 25 min to obtain a reaction solution. Kaolin was added to the above reaction solution and ultrasonically dispersed. The mixture was then stirred at 250 rpm for 3.5 h in a constant temperature water bath at 40 °C. After centrifugation, the mixture was vacuum dried at 60 °C for 24 h to obtain SiO2@kaolin. The weight ratio of KH550, tetraethyl orthosilicate, ethanol, ammonia solution and kaolin was 0.5:10:80:4:5. SiO2@kaolin was added to a toluene solution containing UV absorber UV326 and titanate coupling agent NDZ-201, sonicated at 100W for 30 min, stirred at 180 rpm under a nitrogen atmosphere, and refluxed in an oil bath at 100℃ for 5 h. After filtration, washing, and vacuum drying at 60℃ for 24 h, modified kaolin was obtained. The weight ratio of SiO2@kaolin, UV absorber, toluene, and titanate coupling agent was 1:3.5:100:1. Among them, antioxidants include antioxidant 1010 and antioxidant 168 with a weight ratio of 2:1; The preparation method of aging-resistant insulated power cable includes the following steps: PVC resin, EPDM rubber, ethylene-vinyl acetate copolymer and 1 / 3 part by weight of diisononyl phthalate are mixed at 110°C and 200 rpm for 5 min; modified kaolin, the remaining diisononyl phthalate, stabilizer and antioxidant, polyethylene wax and calcium stearate are added and mixed at 70°C and 45 rpm for 10 min; the mixture is then passed through a two-roll mill at 80°C three times, water-cooled to 40°C and pelletized; the mixture is then extruded using a twin-screw extruder to coat the conductor layer to obtain the aging-resistant insulated power cable. The temperatures of the twin-screw extruder are 145°C in zone I, 160°C in zone II, 170°C in zone III, 180°C in zone IV, and 185°C in the die.
[0023] Example 3 This embodiment provides an aging-resistant insulated power cable, which consists of a conductor layer and an aging-resistant outer sheath layer arranged sequentially from the inside out. The aging-resistant outer sheath layer comprises the following raw materials in parts by weight: 65 parts PVC resin, 30 parts EPDM rubber, 15 parts ethylene-vinyl acetate copolymer, 12 parts modified kaolin, 20 parts diisononyl phthalate, 5 parts calcium-zinc composite stabilizer, 2 parts antioxidant, 1 part polyethylene wax, and 0.7 parts calcium stearate. The modified kaolin is obtained by coating the surface of kaolin with nano-silica to obtain SiO2@kaolin and grafting an ultraviolet absorber. The preparation steps of SiO2@kaolin include: KH550 was mixed with 1 / 10 part by weight of ethanol and stirred at 500 rpm for 15 min to form a silane pre-hydrolyzed solution for later use. Tetraethyl orthosilicate was mixed with the remaining ethanol, the silane pre-hydrolyzed solution was added, and 30% ammonia solution was added. The mixture was stirred at 300 rpm for 30 min to obtain a reaction solution. Kaolin was added to the above reaction solution and ultrasonically dispersed. The mixture was then stirred at 300 rpm for 4.5 h in a constant temperature water bath at 40 °C. After centrifugation, the mixture was vacuum dried at 60 °C for 24 h to obtain SiO2@kaolin. The weight ratio of KH550, tetraethyl orthosilicate, ethanol, ammonia solution and kaolin was 0.7:14:90:5:6. SiO2@kaolin was added to a toluene solution containing UV absorber UV326 and titanate coupling agent NDZ-201, sonicated at 150W for 40 min, stirred at 200 rpm under a nitrogen atmosphere, and refluxed in an oil bath at 110℃ for 6 h. After filtration, washing, and vacuum drying at 60℃ for 24 h, modified kaolin was obtained. The weight ratio of SiO2@kaolin, UV absorber, toluene, and titanate coupling agent was 1.5:4.5:110:1.5. Among them, antioxidants include antioxidant 1010 and antioxidant 168 with a weight ratio of 3:1; The preparation method of aging-resistant insulated power cable includes the following steps: mixing PVC resin, EPDM rubber, ethylene-vinyl acetate copolymer and 1 / 3 part by weight of diisononyl phthalate at 115°C and 250 rpm for 8 min; adding modified kaolin, the remaining diisononyl phthalate, stabilizer and antioxidant, polyethylene wax, and calcium stearate, and mixing at 80°C and 55 rpm for 12 min; passing the mixture through a two-roll mill at 90°C three times, water-cooling to 40°C, and pelletizing; and extruding the mixture using a twin-screw extruder to coat the conductor layer to obtain the aging-resistant insulated power cable. The temperatures of the twin-screw extruder are 150°C in zone I, 165°C in zone II, 175°C in zone III, 185°C in zone IV, and the die temperature is 185°C.
[0024] Example 4 The method is based on Example 1, but with the difference that the silane coupling agent is replaced with KH560.
[0025] Example 5 Based on Example 1, adjustments were made. Unlike Example 1, in the preparation process of modified kaolin, SiO2@kaolin was added to a toluene solution containing titanate coupling agent NDZ-201, ultrasonicated at 120W for 35 min, stirred at 190 rpm under a nitrogen atmosphere, refluxed in an oil bath at 105°C for 5.5 h, filtered, washed, and vacuum dried at 60°C for 24 h to obtain modified kaolin. The weight ratio of SiO2@kaolin, ultraviolet absorber, toluene, and titanate coupling agent was 1.2:105:1.2.
[0026] Example 6 Based on Example 1, adjustments were made. The difference from Example 1 is that the weight of NDZ-201 was adjusted to 0.5 parts during the preparation of modified kaolin.
[0027] Example 7 Based on Example 1, adjustments were made. The difference from Example 1 is that the weight ratio of KH550 to tetraethyl orthosilicate was changed to 1.2:12 during the preparation of modified kaolin.
[0028] Comparative Example 1 The modification was adjusted based on Example 1. Unlike Example 1, the modified kaolin was not grafted with a UV absorber and was replaced with an equal mass of SiO2@kaolin.
[0029] Comparative Example 2 The modification is based on Example 1, except that the modified kaolin is replaced with unmodified kaolin.
[0030] Comparative Example 3 Based on Example 1, adjustments were made. The difference from Example 1 is that the modified kaolin was prepared by adding kaolin to a toluene solution containing UV absorber UV326 and titanate coupling agent NDZ-201, sonicating at 100W for 30 minutes, stirring at 180 rpm under a nitrogen atmosphere, and refluxing in an oil bath at 100°C for 5 hours. After filtration, washing, and vacuum drying at 60°C for 24 hours, the modified kaolin was obtained. The weight ratio of kaolin, UV absorber, toluene, and titanate coupling agent was 1:3.5:100:1.
[0031] Test Example 1: The aging-resistant insulated power cables prepared in Examples 1-7 and Comparative Examples 1-3 were subjected to the following tests: Tensile strength: Tested according to GB / T2951.11-2008; UV aging: The sample was placed in a xenon lamp aging chamber (wavelength 340nm, irradiation intensity 0.35W / m², black standard temperature 60℃, relative humidity 50%) and irradiated for 10 days. Thermo-oxidative aging: The sample was placed in a 100℃ hot air aging chamber for 168 hours. Damp heat aging: The sample was treated at 85℃ / 85%RH for 168h; Calculate the tensile strength retention rate using the following formula; Tensile strength retention rate (%) = Tensile strength after aging / Tensile strength before heat aging × 100%; Thermal cycling delamination: The cable sample is subjected to 100 cycles of hot and cold cycling from -40℃ to 105℃, and the cable sample is observed to see if there is cracking or powdering. The test results are shown in Table 1 below: Table 1
[0032] Based on the aforementioned data, the tensile strength of Examples 1-7 is all within the range of 21.8-22.5 MPa, indicating that adjusting the formulation within this range has little impact on mechanical strength. The tensile strength of Comparative Examples 1-3 is within the range of 20.5-22.0 MPa, with Comparative Example 2 being the lowest, indicating that the kaolin modification effectively improves the filling effect and interfacial bonding, thereby enhancing mechanical properties.
[0033] The retention rates of Examples 1-4 and 6-7 were >90%, thanks to the grafting of the UV absorber UV326 into the modified kaolin. Example 5, lacking the UV absorber, and Comparative Examples 1-3, with no or ineffective grafting, showed significantly lower retention rates, demonstrating that the UV absorber is key to resistance to UV aging. All samples had retention rates >80%, but Examples 1-3 showed the best, and Comparative Example 2 the worst. The SiO2 coating and antioxidants in the modified kaolin synergistically improved thermal stability.
[0034] The trend of humid heat aging is similar to that of thermo-oxidative aging. Examples 1-3 showed a retention rate of >90%, while Comparative Example 2 was the worst. Under humid heat conditions, the hydrophobicity and interfacial bonding of the modified kaolin reduced water penetration and delayed degradation. Furthermore, none of the samples showed cracking or pulverization, indicating that the formulation design provided good thermal cycling stability, unaffected by test conditions.
[0035] Furthermore, the performance of Example 4 decreased slightly due to the difference in coupling efficiency between KH560 and KH550, but the impact was minor. Example 5, lacking a UV absorber, saw a significant drop in UV aging retention to 85.0%, confirming the crucial role of the UV absorber. Example 6, with half the amount of NDZ-201, experienced a slight performance decrease due to insufficient coupling agent leading to reduced grafting efficiency. Example 7 showed a slight performance decrease, possibly due to an imbalance in the silane ratio causing agglomeration. Comparative Example 1, without UV grafting, had a low UV aging retention, but its thermo-oxidative and hygro-thermal retention was higher than Comparative Examples 2-3, as the SiO2 coating still provided a certain barrier. Comparative Example 2, unmodified kaolin, had the worst aging retention, demonstrating its susceptibility to environmental stress erosion. Comparative Example 3 performed better than Comparative Example 2 but worse than the examples, due to uneven dispersion and weak bonding caused by the lack of SiO2 coating.
[0036] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. An aging-resistant insulated power cable, characterized in that, A conductor layer and an aging-resistant outer sheath layer are sequentially arranged from the inside out. The aging-resistant outer sheath layer comprises the following raw materials in parts by weight: 55-65 parts PVC resin, 20-30 parts EPDM rubber, 10-15 parts ethylene-vinyl acetate copolymer, 10-12 parts modified kaolin, 18-20 parts diisononyl phthalate, 4-5 parts calcium-zinc composite stabilizer, 1.5-2 parts antioxidant, 0.5-1 part polyethylene wax, and 0.5-0.7 parts calcium stearate. The modified kaolin is obtained by coating the surface of kaolin with nano-silica to obtain SiO2@kaolin and grafting an ultraviolet absorber.
2. The aging-resistant insulated power cable according to claim 1, characterized in that, The preparation steps of SiO2@kaolin include: mixing KH550 with 1 / 10 parts by weight of ethanol, stirring at 400-500 rpm for 10-15 min to form a silane pre-hydrolyzed solution for later use; mixing tetraethyl orthosilicate with the remaining ethanol, adding the silane pre-hydrolyzed solution, and adding ammonia water, stirring at 250-300 rpm for 25-30 min to obtain a reaction solution; adding kaolin to the aforementioned reaction solution and ultrasonically dispersing it, stirring at 40±2℃ in a constant temperature water bath at 250-300 rpm for 3.5-4.5 h, centrifuging, and vacuum drying to obtain the final product.
3. The aging-resistant insulated power cable according to claim 2, characterized in that, The mass concentration of the ammonia water is 25%-30%.
4. The aging-resistant insulated power cable according to claim 3, characterized in that, The weight ratio of KH550, tetraethyl orthosilicate, ethanol, ammonia and kaolin is 0.5-0.7:10-14:80-90:4-5:5-6.
5. The aging-resistant insulated power cable according to claim 1, characterized in that, The preparation method of the modified kaolin includes the following steps: adding SiO2@kaolin to a toluene solution containing a UV absorber and a titanate coupling agent, sonicating at 100-150W for 30-40 minutes, stirring at 180-200 rpm under a nitrogen atmosphere, and refluxing in an oil bath at 100-110℃ for 5-6 hours, followed by filtration, washing, and drying to obtain the modified kaolin.
6. The aging-resistant insulated power cable according to claim 5, characterized in that, The ultraviolet absorber is UV326; the titanate coupling agent is NDZ-201.
7. The aging-resistant insulated power cable according to claim 6, characterized in that, The weight ratio of SiO2@kaolin, ultraviolet absorber, toluene and titanate coupling agent is 1-1.5:3.5-4.5:100-110:1-1.
5.
8. The aging-resistant insulated power cable according to claim 5, characterized in that, The antioxidants include antioxidant 1010 and antioxidant 168 in a weight ratio of 2-3:
1.
9. A method for preparing an aging-resistant insulated power cable, used to prepare the aging-resistant insulated power cable according to any one of claims 1 to 8, characterized in that, The process includes the following steps: mixing PVC resin, EPDM rubber, ethylene-vinyl acetate copolymer, and 1 / 3 part by weight of diisononyl phthalate at 110-115°C and 200-250 rpm for 5-8 minutes; adding modified kaolin, the remaining diisononyl phthalate, stabilizers and antioxidants, polyethylene wax, and calcium stearate, and mixing at 70-80°C and 45-55 rpm for 10-12 minutes; passing the mixture through a two-roll mill at 80-90°C three times; water-cooling to 40°C and pelletizing; and extruding the mixture using a twin-screw extruder to coat the conductor layer to obtain the aging-resistant insulated power cable.
10. The method for preparing an aging-resistant insulated power cable according to claim 9, characterized in that, The temperature of the twin-screw extruder is 145-150℃ in zone I, 160-165℃ in zone II, 170-175℃ in zone III, 180-185℃ in zone IV, and 185±2℃ in the die head.
Citation Information
Patent Citations
Cross-linked polyethylene power cable nano repairing liquid and repairing method thereof
CN101866706A
High-flame-retardancy high-toughness composite modified PVC (polyvinyl chloride) rubber cable material
CN105566815A
Compound cable material with enhanced weather fastness under synergic effect of inorganic nanometer filler and polypropylene
CN106543521A
High-hardness flame retardant cable material and preparation method thereof
CN108250632A
Wear-resistant and low-temperature-resistant cable material and preparation method thereof
CN109370084A
Cited By
Wear-resistant and aging-resistant cable coating material and preparation method thereof
CN121249073A
Wear-resistant and aging-resistant cable coating material and preparation method thereof
CN121249073B
Weather-proof and waterproof mortar for building and preparation method of weather-proof and waterproof mortar
CN122036286A